From Victimhood to Citizenship : The Path of Roma Integration - Kovats, Martin; Gheorghe, Nicolae; Biró, András (Book collections on Project MUSE., 2013)
The disappointing results of over two decades of activism in the supposedly more liberal climate of post- Communist democracies prompted András Bíró, Hungarian journalist and renowned human rights activist to put down his reflections about the situation of Roma in Eastern Europe. These thoughts in turn stimulated insightful responses from two scholars of the subject: Nicolae Gheorghe, an ethnic Roma living in Romania, and Martin Kovats, among others special advisor on Roma issues to the European Commission in Brussels.